PENGARUH DIVERSI DAN REHABILITASI NON-LAPAS PADA HAK ATAS PEKERJAAN DI SEKTOR PENDIDIKAN SWASTA - Susana De Eba; Emilianus Tena; Siradj Okta (Fakultas Hukum Universitas Katolik Indonesia Atma Jaya, 2023)
Former inmates who have completed their sentences and have been declared free, which includes any individual, face significant challenges in securing employment to meet their livelihood needs. The same situation applies to individuals who have undergone non-prison rehabilitation for drug abuse. Parallel to the experiences of former inmates and non-prison rehabilitation, the concept of diversion has been introduced for juvenile offenders who are prospective job applicants. Both diversion and non-prison rehabilitation share the characteristic that the suspected perpetrators of criminal acts do not undergo punishment through the usual criminal justice system. However, these individuals still face stigma and difficulties similar to those encountered by former inmates in general. This study aims to explore the comparative impact of diversion and non-prison rehabilitation in relation to the right to employment. Specifically, the study focuses on a comparison within the private education sector. Using a comparative approach, this research seeks to provide a sharper perspective on diversion and non-prison rehabilitation as features of modern criminal law in Indonesia. The study finds that within the private education sector, diversion and non-prison rehabilitation offer a more favorable framing for the subjects, supported by philosophical factors inherent in private educational institutions. Policies implemented by the private education sector play a crucial role in ensuring the preservation of the right to employment by educational institutions.